Komunikasi Organisasi antara Pimpinan Asing dan Karyawan Lokal di PT Sunwood Timber Industries - Fitri Amalina; Mochammad Mirza; Riza Gusti Rahayu (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to examine organizational communication between foreign leaders and local employees at PT Sunwood Timber Industries, utilizing a constructivist approach and qualitative research methods, particularly a descriptive case study involving observation, interviews, and document analysis to understand communication patterns and identify barriers in the interaction between these two groups. The study's findings highlight the crucial role of communication in managing cultural differences in the workplace, with effective communication being key to creating an inclusive and productive work environment. The research provides a comprehensive overview and significant contribution to improving organizational communication within the company, offering recommendations for enhancements to enhance the effectiveness of communication between foreign leaders and local employees.